ESTUDIO DE RELACIÓN ENTRE EL ESTRÉS LABORAL Y LA SATISFACCIÓN LABORAL EN LOS TRABAJADORES DEL ÁREA DE PRODUCCIÓN DE UNA INDUSTRIA DE TUNGURAHUA: CASO PRODEGEL S.A. - Albán Marañón, Ismael Andrés (2018)
This investigation is a correlational analysis between work stress and job satisfaction variables on workers of the production area of an industry in the province of Tungurahua. The research was carried out on a population of 76 employees that belong specifically to the production or manufacture area of the company PRODEGEL S.A. Two evaluation tools were used to obtain data related to both, job stress and job satisfaction, as well as a sociodemographic sheet that allowed obtaining certain data from the population of interest. Through the result analysis, it was found that there is a significant but not determinant relationship between work stress and job satisfaction, which indicates that in this specific population, both work stress and job satisfaction are strongly determined by other aspects, which is probably due to a circular or also called cellular model of organization on which the employees of the production area managed and organized.